2011 IEEE International Symposium on a World of Wireless, Mobile and Multimedia Networks 2011
DOI: 10.1109/wowmom.2011.5986473
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent transportation systems: When is safety information relevant?

Abstract: Abstract-In this paper, we compare two methods of estimating relevance for the emergency electronic brake light application. One uses an analytically derived formula based on the minimal safety gap required to avoid a collision. The other method uses a machine learning approach. The application works by disseminating reports about vehicles that are performing emergency deceleration in effort to warn drivers about the need to perform emergency braking. Vehicles which receive such reports have to decide whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The method has been shown to outperform heuristic or analytic approaches (20,21). In particular, this method is based on work by the authors on EEBL applications (20) in which machine-learning techniques are used to learn a relevance estimator and compare it with an analytic approach. However, the method described earlier was specific to EEBLs (20).…”
Section: Relevant Literaturementioning
confidence: 99%
“…The method has been shown to outperform heuristic or analytic approaches (20,21). In particular, this method is based on work by the authors on EEBL applications (20) in which machine-learning techniques are used to learn a relevance estimator and compare it with an analytic approach. However, the method described earlier was specific to EEBLs (20).…”
Section: Relevant Literaturementioning
confidence: 99%
“…The results showed that, by learning of parking availability, vehicles made better selections among the different parking availability reports and lowered the time that it took them to find a parking space. In [15], the machine learning approach was proposed for use in the EEBL application. This paper presents the further development of that work by showing how the machine learning methods can handle multiple lane roads, presenting further testing of wireless communication parameters, and providing a methodology for setting the system parameters.…”
Section: Relevant Workmentioning
confidence: 99%
“…The tools provide an ability to evaluate the safety benefit of the application for the learned relevance estimation model. The platform is based on the Observe-Driverand-Learn (ODaLe) principle, which is a method for learning the relevance of information that has previously been used for safety [4] and non-safety applications [5]. The idea is to observe the driver's reaction after a report was generated by the application and use this information as an input to a machine learning algorithm.…”
Section: The Platformmentioning
confidence: 99%